2014
DOI: 10.1007/s11571-014-9325-x
|View full text |Cite
|
Sign up to set email alerts
|

Power spectral density and coherence analysis of Alzheimer’s EEG

Abstract: In this paper, we investigate the abnormalities of electroencephalograph (EEG) signals in the Alzheimer's disease (AD) by analyzing 16-scalp electrodes EEG signals and make a comparison with the normal controls. The power spectral density (PSD) which represents the power distribution of EEG series in the frequency domain is used to evaluate the abnormalities of AD brain. Spectrum analysis based on autoregressive Burg method shows that the relative PSD of AD group is increased in the theta frequency band while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(93 citation statements)
references
References 74 publications
(88 reference statements)
5
78
0
Order By: Relevance
“…Power analysis of source-reconstructed MEG signals confirmed the characteristic changes in the oscillatory activity of AD subjects compared to HC subjects ( Fig. 2a) (53)(54)(55)(56). Significant alpha power decreases were more evident in the parietal and occipital regions (Z < −2.58), while significant delta power increases (Z > 2.58) were more localized in the frontal regions of the cortex (Fig.…”
Section: Resultssupporting
confidence: 53%
“…Power analysis of source-reconstructed MEG signals confirmed the characteristic changes in the oscillatory activity of AD subjects compared to HC subjects ( Fig. 2a) (53)(54)(55)(56). Significant alpha power decreases were more evident in the parietal and occipital regions (Z < −2.58), while significant delta power increases (Z > 2.58) were more localized in the frontal regions of the cortex (Fig.…”
Section: Resultssupporting
confidence: 53%
“…Studies regarding EEG total power spectral densities, as well as spectral densities of individual frequency bands is a concept not strictly confined to epilepsy, but also widely applicable to studies of Alzheimer's disease and generalized anxiety disorder (32,33). The study about Alzheimer's disease has noted reduction in high-frequency and increase in low-frequency bands, much like the results this study yielded.…”
Section: Discussionsupporting
confidence: 55%
“…Mutual information analysis also showed that connections between the frontal and antero-temporal regions are weaker in AD patients [41]. Recent coherence studies using complex network analysis also support collapsed connectivity in the θ and α frequency bands [42,43]. Interestingly, in contrast to the decreased connectivity observed in AD patients, coherence increased in the θ, high β, and γ frequency bands in PD patients [44,45].…”
Section: Discussionmentioning
confidence: 87%